A multi-component reaction mechanism of n-butanol, n-octanol, and di-n-buthylether for engine combustion. (1st September 2020) - Li, Jing; Zhou, Dezhi; Yang, Wenming
Abstract: The purpose of this study is to develop a multi-component skeletal mechanism including renewable fuels of n-butanol, n-octanol, and DnBE (di-n-buthylether) for engine combustion. Mechanism reductions using the directed relation graph, directed relation graph with error propagation and sensitivity analysis, peak concentration analysis, and isomer lumping methods were first carried out on the detailed reaction mechanisms for each type of the fuels. Then, the obtained single-fuel skeletal mechanisms were combined to construct the multi-component skeletal mechanism. Finally, the developed reaction mechanism, which consisting of 117 species and 610 elementary reactions, was obtained. To validate the fuel model, calculations on ignition delay times for each component of the skeletal mechanism, species concentrations in JSR for n-octanol, laminar flame speeds for DnBE, and 3-D diesel engine combustion fueled with n-octanol and DnBE were carried out. Results demonstrated that the predicted ignition delay times can well match the data given by detailed mechanisms and experiments under the conditions covering a wide range of temperatures, pressures, and equivalence ratios. Also, the concentration profiles of important species in a jet stirred reactor were well reproduced by the skeletal mechanism with equivalence ratios of 0.5, 1.0, and 2.0. The laminar flame speeds of DnBE were also in good agreement with experimental data at 1 atm with a wide range of equivalence ratios. For diesel engine simulations fueled with n-octanol and DnBE, with different engine speeds and loads, both in-cylinder pressure traces and heat release rate profiles can be well represented by the present skeletal reaction mechanism.